2014
DOI: 10.1186/1745-6215-15-295
|View full text |Cite
|
Sign up to set email alerts
|

Baclofen for stroke patients with persistent hiccups: a randomized, double-blind, placebo-controlled trial

Abstract: BackgroundThe results of preclinical studies suggest that baclofen may be useful in the treatment of stroke patients with persistent hiccups. This study was aimed to assess the possible efficacy of baclofen for the treatment of persistent hiccups after stroke.MethodsIn total, 30 stroke patients with persistent hiccups were randomly assigned to receive baclofen (n = 15) or a placebo (n = 15) in a double-blind, parallel-group trial. Participants in the baclofen group received 10 mg baclofen 3 times daily for 5 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 25 publications
0
39
0
Order By: Relevance
“…The result of this study showed that baclofen was more effective than placebo (p=0.003) 13. There were no significant adverse effects, other than one case of each mild transient drowsiness and dizziness.…”
Section: Treatment Of Hiccupsmentioning
confidence: 64%
See 1 more Smart Citation
“…The result of this study showed that baclofen was more effective than placebo (p=0.003) 13. There were no significant adverse effects, other than one case of each mild transient drowsiness and dizziness.…”
Section: Treatment Of Hiccupsmentioning
confidence: 64%
“…A randomised controlled trial by Zhang et al 13 compared baclofen, which is a GABA B (gamma-aminobutyric acid) receptor agonist (10 mg three times a day for 5 days), and placebo for the treatment of persistent hiccups in 30 patients with stroke. The result of this study showed that baclofen was more effective than placebo (p=0.003) 13.…”
Section: Treatment Of Hiccupsmentioning
confidence: 99%
“…fatigue, sedation, dizziness) were not reported by all studies; however, it is clear that these can be associated with all medications with efficacy in hiccups. When reported, the frequency of side effects was up to 50% for neuroleptic medications and this appeared to be more frequent for chlorpromazine and metoclopramide than for baclofen at standard doses or gabapentin . Very little data was available for other medications.…”
Section: Resultsmentioning
confidence: 99%
“…It has also central and peripheral effects on vagal efferent nerves that inhibit transient relaxations of the lower oesophageal sphincter and diaphragm with effects also on the oesophago‐gastric junction that suppress reflux after meals . Several reports, including one randomised controlled trial, suggest that baclofen can terminate hiccups . Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Baclofen has been used to treat hiccups in various clinical settings. Zhang et al [6] studied patients with cerebrovascular accident and persistent hiccups and randomized 30 patients to receive baclofen 10 mg 3 times per day or placebo. Hiccups resolved in all but 1 of the patients in the treatment group, and hiccups continued in all but 2 subjects of the placebo group.…”
Section: Introductionmentioning
confidence: 99%